Transcrystallinity versus spherulitic crystallization in polyamide 66: An experimental study. Issue 1 (31st October 2018) - Freire, Lionel; Combeaud, Christelle; Monge, Gabriel; Billon, Noëlle; Haudin, Jean‐Marc
Abstract: The crystallization of 3 polyamides 66 has been studied by optical microscopy and differential scanning calorimetry (DSC). Nonisothermal crystallization kinetics has been analyzed using Ozawa's equation. Two polymers have close behaviors with a crystallization mainly spherulitic. The third one, which has the highest molar mass, is subject to intense transcrystallinity, which disturbs the crystallization kinetics (shoulder on the DSC curves and low Avrami exponent). For this polymer, original methods based on a detailed analysis of transcrystallinity have been applied to measure crystal growth rate and to determine the "intrinsic" crystallization kinetics, that is, not polluted by transcrystallinity. Abstract : This paper studied the competition between spherulitic crystallization and transcrystallinity in polyamide 66 by combining optical microscopy and DSC. The influence of transcrystallinity on overall crystallization kinetics is analyzed. In the case of intense transcrystallinity, an original method for growth‐rate measurements is applied. Its results compare well with those given by other methods and with literature data. Finally, the "intrinsic" crystallization kinetics of the polymer, that is, not disturbed by transcrystallinity, is determined.